STUDENTS ERRORS IN POSITIONING CONJUNCTION IN WRITING ESSAY - Yusti, Dwi Intan (Journal of English Teaching and Linguistics Studies (JET Li), 2022)
Abstract Conjunction plays an important element in communication which acts as a connector between clauses with other clauses. Some students still make errors in positioning conjunction in writing. This research aimed  to identify students errors in positioning conjunction in writing essay. This research is conducted to the fifth semester students of English Language Education Study Program, Faculty of Teacher Training Educational Sciences, Pakuan University. There were 20 students who become the participants. The writer uses descriptive method to analyze students error in positioning conjunction. The data are collected by using students work, questionnaire, and interview note. There are four types of error: omission, addition, misformation, and misordering. From the result of the research, it is found that the highest error is misformation. There are (50,6%) misformation errors. Addition appears as the second error (34,5%). The third error comes from omission (11,5%) and the lowest error is misordering (3,4%).